Sustainability of Fish Fillet Processing Industries in Batang District - Astrid Fauzia Dewinta; Widodo Farid Ma'ruf (Jurnal Ilmiah Perikanan dan Kelautan, 2020)
HighlightsSustainability index from fish fillet industry is important to know because a fishing industry just not looking for feasibility study in economic dimension but all dimension (resources, technology, social, legal and institutional)Multidimension sustainability index from fish fillet processing industry in Batang is included in the category of "Self Sustainable” with a value of 50.39  The dimensions causes of the low sustainability in fish fillet industry are social, legal and institutional, and technology with the value of each dimension that is 48.6; 40.27; 48.9 in means "less sustainable”AbstractThe existence of fish fillet processing industries in Batang are able to have a positive impact on the surrounding community because it can create employment opportunities and increase community income. Therefore, it is necessary to know the importance of the sustainability of fish fillet processing industries to see the prospect of fishery business after a feasibility study. The aims of this study were to analyze the sustainability index value, determine the sensitive attributes of each dimension, and provide alternative management strategies of fish fillet processing industries in Batang. The method of analysis used was Rapfish method which is based on the technique of ordination by putting something measured using MDS on the program of Rapfish G77 Alscal program (VBA and Excel). Status management of fish fillet processing industries sustainability in Batang, which are multidimensionally sustainable, are 50.39. Whereas in other dimensions such as resources 58.20 (quite sustainable), economic 55.33 (fairly continuous), social 48.60 (less sustainable), legal and institutional 40.27 (less sustainable) and technological 48.90 (less sustainable). Based on this results, several management strategies should be prepared including increasing the capacity of government institutions, enhancing the role of fish fillet processing industry on society, increasing the application of technology and infrastructure, increasing the revenue of the entrepreneurs of fish fillet processing industry, preventing decline of quality and quantity of fish resources.